The Impacts of “A Plastic Ocean” Film on The Environmental Care Attitudes of Senior High School Students in Tangerang - Suraya Mansur; Nurhayani Saragih; Rohana Binti Mijan (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2023)
This research examines the impacts of “A Plastic Ocean” film on the environmental care attitudes of Senior High School students at SMAN 2 Tangerang. This research proves that the social learning theory is effective to promote a campaign with film, which results in behavioral changes in society. The theory used in this research is Albert Bandura's social learning theory. This research utilized the positivistic paradigm. This research employed a survey explanatory method and quantitative approach. The population was Senior High school Students at SMAN 2 Tangerang. The sampling utilize a purposive sampling technique to 100 respondents, with a sampling error of 5%. The technique of data analysis utilized a simple regression analysis. The hypothesis how that there is no influence between the content of the “A Plastic Ocean” film on environmental care attitudes on students. High school students are interested in the film, while the attitude of caring for the environment is not influenced by the film.